A risk perspective on market integration and the reform of support of renewables in Germany - Michael Pahle; Henriette Schweizerhof (Potsdam Institute for Climate Impact Research (PIK), 2015)
After more than a decade of supporting power from renewable energy (RE) through guaranteed feed-in tariffs, the German Government has initiated reforms to integrate RE into the market. To eventually achieve market integration requires that RE investors carry power market risks, in particular the power price risk. At the same time however, under the current financial structure higher risks are likely to have a negative impact on the bankability of new RE projects, which by extension may endanger further deployment and the achievement of renewable targets with it. Against this background we take a risk perspective to assess the past and upcoming EEG reforms, with the aim of developing a proposal to gradually shift risk towards RE investors without endangering project finance. To that end we first discuss the case for more market risk and classify the specific respective risks for RE, analyze how they have been allocated so far, and find that past policy reforms have initiated only a marginal transfer of revenue risks to renewables. On that basis we argue that more ambitious steps in this direction need to be taken, for which regulatory complexity and reform outcome uncertainty suggest a continuous and transparent transition rather than a grand all-at-once intervention. We outline and discuss two elements that could be at the center of it: First, a support framework that creates incentives for RE projects to increasingly take risks, for which we propose a cascading risk auction mechanism that prioritizes “more risky” projects. Second, design options for (a) “more risky” support contracts and (b) risk transfer in power purchase contracts, which if standardized could help to develop and establish suitable risk mitigation and management approaches on the side of financers. While this paper does not deliver a fully spelled-out action plan for these elements, it provides a basic sketch and identifies the main research gaps that should be filled for implementing it. Giving the long lead times of reforms and the need to think ahead that arises from it, we are sure that this proposal can make an important contribution to the next EEG reform in Germany expected for 2016/2017.
Keywords: D81; Q28; Q42; Q58; 330; Germany; renewable support; risk